The Effect of Round Robin Technique and Anxiety Toward Students Speaking Achievement at Fort De Kock Nursing Academy - Abizar Giffari (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to explain the effect of Round Robin techniques and student anxiety on speaking ability. The design of this study was a quasi-experimental study with a factorial 2x2 design. The population of this study was first-level students at the Health Academy of Fort De Kock Bukittinggi. The ability to speak and the anxiety level questionnaire was used as a data collection tool for this study. Furthermore, the research data was by using the T-test formula and two-way ANOVA. The results showed that (1) groups of students with Round Robin techniques had better speaking skills than students with Memorization techniques, (2) groups of students with high anxiety with Round Robin technique has better speaking skills than Memorization techniques, (3) groups of students with low anxiety with Round Robin technique have good speaking skills from Memorization techniques and (4) there is no interaction between the two and anxiety towards students' speaking ability, where Fcount (0.0251) is lower than Ftable (4.96).